Analisis Diferensiasi Sertifikasi Tenaga Kerja Pariwisata Standar Internasional dan Nasional Pada Program KSATRIA - Habibah Madzin Yusufiah; Supriyadi, Tedi; Putra, Gilang Pratama (Universitas Muhammadiyah Pontianak, 2026)
This study examines the differentiation of tourism workforce certification based on ASEAN MRA-TP and SKKNI standards within the KSATRIA Program to strengthen the competitiveness of Indonesia’s tourism human resources. A descriptive comparative quantitative approach was applied using secondary data from the 2025 KSATRIA Program. Data were analyzed using descriptive statistics, cross-tabulation, and Chi-Square tests with SPSS software. The results show that certification remains dominated by SKKNI standards with significant regional differences. These findings highlight gaps in ASEAN MRA-TP implementation and provide empirical support for strengthening ASEAN-aligned certification to improve workforce competitiveness and regional mobility readiness. Keywords: ASEAN MRA-TP; Competitiveness; Certification; SKKNI; Tourism